Determinants of cervical high-risk human papillomavirus positivity among Rwandan women living with human immunodeficiency virus - Gad Murenzi; Faustin Kanyabwisha; Maria Demarco; Benjamin Muhoza; Kristen Hansen; Jean Paul Mivumbi; Anthere Murangwa; Theogene Rurangwa; Thierry Muvunyi Zawadi; Gallican Kubwimana; Julia C. Gage; Tiffany Hébert; et al. (PLoS ONE, 2025)
Introduction There are few data on the prevalence of cervical high-risk human papillomavirus (hrHPV), the necessary cause of cervical cancer, and its determinants among Rwandan women living with human immunodeficiency virus (HIV). We therefore aimed to assess the determinants of hrHPV positivity among Rwandan women living with HIV (WLWH). Methods We conducted a cervical cancer screening study of ~5,000 WLWH aged 30–54 years and living in Kigali, Rwanda, but originally from all provinces in the country, from 2016–2018. Women were tested for hrHPV by the Xpert assay (Cepheid, Sunnyvale, CA, USA). A nurse-administered questionnaire collected data on demographics and HPV/cervical cancer risk factors. Women without evidence of cervical precancer and cancer were included in the analysis. Results Women included in this analysis (N = 4,880) had a mean age of 40 years, > 98% were on antiretroviral therapy, and 61% had a CD4 count of ≥500 cells/µL. High-risk HPV prevalence was 25.5% [95% confidence interval (CI)=24.3%−26.8%] and the prevalence decreased with older ages and higher CD4 counts (ptrend<0.001 for both). High-risk HPV prevalence was higher for those who reported their first sex before 16 years, had their first child before 18 years, had more sexual partners over their lifetime and in the last six months, and those with lower CD4 cell count (ptrend<0.001 for all). A CD4 count of <200 (vs. > 500) per µL was most strongly associated with being hrHPV positive (adjusted odds ratio = 2.7, 95%CI = 2.1–3.6). Conclusions Our findings highlight the role of CD4 counts, as a measure of HIV control and immunity, in controlling hrHPV infection, which could potentially impact cervical cancer control among this high-risk population. Raising awareness on various associated factors coupled with integrating HPV and cervical cancer awareness in HIV care could help control this double burden of disease.